2015
DOI: 10.1016/j.jhep.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Mouse hepatocytes and LSEC proteome reveal novel mechanisms of ischemia/reperfusion damage and protection by A2aR stimulation

Abstract: IR and A2aR stimulation produces pathological and protected liver cell phenotypes, respectively characterized by down- and upregulation of proteins involved in the response to O2 and nutrients deprivation during ischemia, oxidative stress, and reactivation of aerobic energy synthesis at reperfusion. This provides novel insights into IR hepatocellular damage and protection, and suggests additional therapeutic options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…55 Both A2A and A2B have been shown to be involved in prevention of liver IRI. 56,57 Human hepatic cDCs express comparatively high levels of CD39 compared with blood-borne cDCs. 58 Interestingly, CD39 expression by mouse hepatic cDCs attenuates inflammation in liver cold IRI 58 and CD39-deficient liver grafts suffer worse IRI due to increased inflammatory activation of cDCs.…”
Section: Hdc-mediated Anti-inflammatory Responses In Liver Ischemia-rmentioning
confidence: 99%
“…55 Both A2A and A2B have been shown to be involved in prevention of liver IRI. 56,57 Human hepatic cDCs express comparatively high levels of CD39 compared with blood-borne cDCs. 58 Interestingly, CD39 expression by mouse hepatic cDCs attenuates inflammation in liver cold IRI 58 and CD39-deficient liver grafts suffer worse IRI due to increased inflammatory activation of cDCs.…”
Section: Hdc-mediated Anti-inflammatory Responses In Liver Ischemia-rmentioning
confidence: 99%
“…Oxidative stress is a phenomenon caused by an imbalance between the production of free radicals (species with one or more unpaired electrons), reactive metabolites, or ROS and their elimination through antioxidant mechanisms [25][26][27]. Oxidative stress is able to modify the phenotype of many hepatic cell types including hepatocytes, HSC, and inflammatory cells [28], but LSEC are probably the most sensitive liver cell type to oxidative stress [29,30] due to several reasons: first, ROS have been described as key drivers in the initiation of liver injury and LSEC response [30][31][32][33]; second, ROS selectively damage LSEC and alter LSEC phenotype during liver injury [20,27,29]; and third, LSEC are prone to oxidative stress due to a reduction in their enzymatic detoxifying capacity of H 2 O 2 [34][35][36]. In addition to the classical antioxidant response, LSEC have additional mechanisms, such as autophagy (a degradation process that maintains LSEC homeostasis), able to detoxify oxidative species and necessary for a proper adaptive response to stress.…”
Section: Triggers For Lsec Dysfunctionmentioning
confidence: 99%
“…However, the comparison of the LSEC populations obtained by CD146+ MACS to our technique showed that significant higher proportions of macrophages (4.85±1.11%) and unidentified cells (9.20±2.63%) were still present in the final cell population using the CD146+ MACS technique. To increase purity of LSEC isolated using this method, some authors optimized the procedure by adding a CD45magnetic sorting to remove blood cells [29,56]. Further, we observed a decreased viability in the population obtained by the CD146+ MACS technique, suggesting that the positive sorting either led to a non-specific retention of dead cells or decreased cell viability.…”
Section: Discussionmentioning
confidence: 86%